The Effect of Health Education on Lactation Management using Audiovisual Media on The Level of Knowledge of Mother Cadres - Hairunnissa, Hairunnissa; Mirandha Wiguna, Adelia (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: This study was to determine the level of knowledge about lactation management with audiovisual media on cadres. Methods: This research design uses descriptive research with a case study approach to 30 respondents with an age range of 25-50 years. Results: The results showed an increase in good knowledge with a percentage of 100%. Conclusions: From the results of the research conducted, it can be concluded that there is an increase in knowledge about lactation management using audiovisual media after health counselling.